50. Inter hemispheric comparison of PAS-induced cortical plasticity: A pilot study in healthy subjects. Issue 12 (December 2017) - Rispoli, V.; Diozzi, E.; Villani, G.; Capone, J.G.; Sette, E.; Simioni, V.; Tugnoli, V.
Abstract : Dystonia is considered a "network" disease with an abnormal cortical plasticity induced by by paired-associated-stimulation. In this study, we applied the PAS-TMS paradigm in healthy subjects, with the aim to collect reliable data from both hemispheres in order to put the basis to future application in focal dystonia. We studied 7 healthy subjects (4 females; mean age 32.33 ± 6.79 years). We applied electrical stimulatrion of median nerve electrical and MEPs from both abductor pollicis brevis (APB) and first dorsal interosseous (FDI) muscles (2), following Stefan et al. technique, with ISI set to 25 ms. MEPs before and after PAS protocol, evaluating first the dominant and then controlateral motor cortical area. Every subject performed the study in the same experimental session. Comparison between MEPs before and after PAS on homologous hemisphere disclosed a trend toward an increased of amplitude, but without reaching statistical significance for both ABP and FDI muscles, according to Quartarone et al. At the same time, no significant difference was detected by evaluating paired inter-hemisphere analysis. These bilateral findings in normal subjects could be a possible beginning for future application on focal movement disorders.